2021
DOI: 10.3174/ajnr.a7102
|View full text |Cite
|
Sign up to set email alerts
|

Novel Human Acute Ischemic Stroke Blood Clot Analogs for In Vitro Thrombectomy Testing

Abstract: BACKGROUND AND PURPOSE: Previous studies have successfully created blood clot analogs for in vitro endovascular device testing using animal blood of various species. Blood components vary greatly among species; therefore, creating clot analogs from human blood is likely a more accurate representation of thrombi formed in the human vasculature. MATERIALS AND METHODS:Following approval from the Mayo Clinic institutional review board, human whole-blood and platelet donations were obtained from the blood transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…4 Coagulation was induced by adding 1 mL of 5% calcium chloride and 10 mL of 10 U/mL thrombin per 10 mL of blood mixture. 7 To simulate LVO, we loaded clot analogs into a syringe and embolized them to the brain via a 0.088-inch guide catheter (Neuron MAX; Penumbra) under physiologic pressure. This clot analog was selected to challenge current thrombectomy devices because fibrin-rich clots have been reported to be associated with more device passes, longer procedure times, and less favorable patient outcomes.…”
Section: Recreation Of Large-vessel Occlusionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Coagulation was induced by adding 1 mL of 5% calcium chloride and 10 mL of 10 U/mL thrombin per 10 mL of blood mixture. 7 To simulate LVO, we loaded clot analogs into a syringe and embolized them to the brain via a 0.088-inch guide catheter (Neuron MAX; Penumbra) under physiologic pressure. This clot analog was selected to challenge current thrombectomy devices because fibrin-rich clots have been reported to be associated with more device passes, longer procedure times, and less favorable patient outcomes.…”
Section: Recreation Of Large-vessel Occlusionmentioning
confidence: 99%
“…8 Clot analogs with different histology and tensile properties can also be made by mixing human plasma and red blood cells with different volume ratios. 7,9 Thrombectomy Testing Thrombectomy was performed with a 6F catheter (Sofia Plus; MicroVention) using the direct-aspiration technique or in combination with a stent retriever (Solitaire; Medtronic) using the Solumbra technique. These 2 techniques were selected because they are most often used for thrombectomy on the basis of a survey of neurointerventionalists.…”
Section: Recreation Of Large-vessel Occlusionmentioning
confidence: 99%
“…The composition of occlusive clots in acute ischemic stroke has received vast attention through two dimensional (2D) histopathology investigations ( 1 3 ). Knowledge about human clots composition allowed valuable developments regarding the preparation of clot analogs ( 4 ) which best reproduce in terms of cellular and fibrin content the composition of clots retrieved from patients. Clot analogs with predefined compositions were successfully used to define the most effective clinical imaging protocols, computed tomography (CT) ( 5 ) or magnetic resonance imaging (MRI) ( 6 ), or to study in vitro thrombectomy techniques ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about human clots composition allowed valuable developments regarding the preparation of clot analogs ( 4 ) which best reproduce in terms of cellular and fibrin content the composition of clots retrieved from patients. Clot analogs with predefined compositions were successfully used to define the most effective clinical imaging protocols, computed tomography (CT) ( 5 ) or magnetic resonance imaging (MRI) ( 6 ), or to study in vitro thrombectomy techniques ( 4 ). While clot analogs are a valuable tool for studying clinical imaging and optimizing interventional techniques, the clots retrieved from patients remain the most valuable substrate for research on clot behavior ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is important to characterize the clot ex vivo with imaging techniques similar to those used in clinical setting. Recently, the preparation of analog clots series ( 35 ), spanning a wide range of red blood cells, fibrin, and platelets content, allowed the development of parametric studies which identified MRI sequences ( 36 ) and CT protocols ( 37 ) capable of differentiating different clot types in vitro .…”
Section: Introductionmentioning
confidence: 99%